Effect of row spacing on seed quality attributes and seed yield in rice (Oryza sativa) cultivar 'Pusa Sugandh-5' - Singh, K.K.; Singh, Y.V.; Sharma, S.K.; Singh, Pratiksha (Annals of Agricultural Research, 2019)
A field study on the effect of row spacing on seed yield and seed quality attributes in rice cv. 'Pusa Sugandh-5' were taken up at ICAR- IARI, New Delhi during kharif 2008-09 and 2009-10. Treatment included six row spacings viz., 30 cm × 20 cm, 30 cm × 15 cm, 30 cm × 10 cm, 20 cm × 20 cm, 20 cm × 15 cm and 20 cm × 10 cm with three replications placed under randomized block design (RBD). The observations on various yield contributing parameters, yield, quality attributes and vigour index were recorded. Results showed that row spacing of 30 × 20 cm was significantly superior in term of seed yield and other characters viz. number of total productive tiller/hill, days to 50% flowering, test weight, filled grain/panicle, seed recovery, seed moisture and harvest index. Seed obtained from 30 cm × 20 cm spacing showed significantly higher germination percentage, seedling dry weight, root length, shoot length, total seedling length, per seedling dry weight, vigour index- I and vigour index- II compared to other row spacing treatments.